Customary Refugee Law - Lambert, Hélène (The Oxford Handbook of International Refugee Law, 2021)
This chapter explores customary refugee law. Refugee law is primarily treaty law. However, many of the major refugee-receiving countries are not parties to either the Refugee Convention or the Refugee Protocol, for example Bangladesh, Pakistan, India, Iran, Jordan, and Lebanon. Hence, customary international refugee law can be critically important in the identification of key principles of refugee protection and as an indication of what is permitted or not. While customary international law may not play as significant a role in refugee law as it does in other areas of international law, there are at least three practices of refugee protection aimed at safeguarding access and admission to refugee protection for which varying degrees of agreement exist in favour of a rule (or emerging rule) of customary law: non-refoulement, temporary refuge, and the right to be granted (to receive) asylum. These practices are deeply intertwined in their humanitarian purpose.